(untitled) (Sustainability in Debate, 2016)
The objective of this article is to develop a computer-based simulation model of the use of scrap tire waste in the composition of interlocking concrete blocks. Research was carried out by means of a computer simulation of variations occurring in constituent basic elements of concrete blocks by the insertion of waste tires. Two scenarios were elaborated for the projection of results and Vensim software (VENTANA SYSTEMS, 2011) was used. The main results of the article are there is an economy of 15.71% of water in scenario A and 9.42% in scenario B; and an economy of 6.79% of cement in scenario A and 0.77% in scenario B. Finally, we emphasize consumption of 473 tons of scrap in the simulation done in scenario B and 372 tons in scenario A. This suggests that there should be encouragement of the use of pneumatic waste in building concrete blocks.